Wine Representation in Literature: Chile, Argentina and Peru (1850-1930) [Representaciones del Vino en la Literatura: Chile, Argentina y Perú (1850-1930)] - Cussen-Abud, F; Lacoste, P (Universidad Catolica Silva Henriquez, 2022)
The contribution of literature to the process of construction of the image of wine in the three countries historically most relevant in Latin American viticulture: Peru, Chile and Argentina is studied in this article. The representations of wine in the narratives of these three countries during the foundational period of national literatures, from the mid-19th century to the beginning of the 20th century, are investigated. A documentary corpus was formed with fifty works from the three countries, in order to identify the space dedicated to the regional and European wine heritage. The works of popular European literature of the time, especially the action novels of Alexandre Dumas and Emilio Salgari, were used as a frame of reference. It is found that, while European writers were interested in making visible, promoting and enhancing the value of Old-World heritage wines, Latin American writers, on the contrary, instead of enhancing the value of regional wines, chose to consolidate the hegemonic paradigm of European viticulture. © 2022 Universidad Catolica Silva Henriquez. All rights reserved.